20 Reappraising remodelling pattern of left ventricle in aortic stenosis: axis orientation as a unique signature of positive remodelling. (May 2019) - Chan, Kenneth; Mahmod, Masliza; Zacur, Ernesto; Rigolli, Marzia; D'Souza, Michelle; Francis, Jane; Ariga, Rina; Raman, Betty; Dass, Sairia; Karamitsos, Theodoros; Neubauer, Stefan; Myerson, Saul; et al.
Abstract : Introduction: In aortic stenosis (AS), characterisation of ventricular (LV) remodelling beyond left ventricular mass measurements is lacking. We sought to study the 3-dimensional (3D) geometric LV remodelling pattern in severe AS pre- and post-surgical aortic valve replacement (AVR), and compared it with hypertensive and healthy controls. Methods: Ninety-one subjects (36 severe AS, 19 hypertension and 36 healthy controls) underwent cardiac magnetic resonance (CMR). 18 AS patients had a repeat CMR eight-month post-AVR. 3D meshes were reconstructed from the myocardial contours of the CMR cine images. Principle component analysis and linear discrimination analysis were used to derive shape coefficients. Results: AS patients had a significant shift in LV axis and apex orientation towards the septum, and more spherical LV shape which were not seen in the hypertensive and healthy control groups. As expected severe AS was associated with thicker and larger LV compared to the other two groups. Post AVR, despite significant reduction in LV thickness and sphericity, interestingly the shift in the LV axis/orientation was unchanged/irreversible (Figure 1 ). Conclusion: Severe AS is characterised by unique remodelling pattern which is not reversible post AVR. The novel shape metrics that comprehensively quantify the LV morphology may be a potential marker for risk stratification in the management of AS. Conflict of Interest: none